The body politic and the political body in nationalist science: Physical education at Stellenbosch University in the 1930s (Yesterday & Today Journal for History Education in South Africa and abroad, 2023)
Stellenbosch University (SU) was the first university in Africa to introduce a dedicated physical education certificate course in 1937. In defining the Physical Education Department’s raison d’etre, the first head of the department, Dr Ernst Jokl, declared that his main aim was to transform SU into the recognised centre for scientific physical education in South Africa. Beyond this purpose, the institutionalisation of physical education resonated with the institution’s Afrikaner-nationalist ethos. At the volksuniversiteit, standardised physical education was intended to contribute to the strengthening of the corporate and individual Afrikaner body. While Jokl played a pivotal role in the establishment of standardised physical education at SU, his tenure was abruptly terminated following controversy surrounding medical examinations of female physical education students. In examining the events that led up to Jokl’s swift departure, we explore the origins of physical education at SU and the ways in which the university’s institutional culture shaped the trajectory of this nascent discipline. In essence, we argue that Jokl’s exit was precipitated by his ‘scientific methods’ that required students to undress for their medical inspections. While all the students underwent the same examination, the uproar was rooted in the fact that women students were subjected to the inspections. While he argued that his approach was an extension of his scientific endeavours, Jokl transgressed the traditionalist and strongly gendered values of SU and the idealised Afrikaner nation that it sought to both represent and shape.
Keywords: Physical education; Gender; Afrikaner nationalism; Volksuniversiteit; Volk; Stellenbosch University